The effects of sumac (Rhus coriaria L.) powder supplementation in patients with non-alcoholic fatty liver disease: A randomized controlled trial. (November 2020) - Kazemi, Samira; Shidfar, Farzad; Ehsani, Simin; Adibi, Peyman; Janani, Leila; Eslami, Omid
Abstract: Background: In recent years, great attention has been paid to the role of herbal medicine in the management of non-alcoholic fatty liver disease (NAFLD). Sumac ( Rhus coriaria L.) is a popular herb which contains major bioactive compounds known for a variety of health benefits. This study aimed to assess the effects of sumac powder supplementation on hepatic fibrosis and some metabolic markers in patients with NAFLD. Methods: Eighty-four patients diagnosed with NAFLD were included in this randomized double-blind placebo-controlled clinical trial. They were randomly assigned to receive 2000 mg per day sumac powder (n = 42) or placebo (n = 42) for 12 weeks. Also, both groups received a 500-calories deficit diet plan. Hepatic fibrosis and liver enzymes (ALT and AST) as well as fasting blood sugar (FBS), serum insulin, HbA1c, HOMA-IR (insulin resistance index), QUICKI (insulin sensitivity index), malondialdehyde (MDA), and high sensitivity C-reactive protein (hs-CRP) were measured at baseline and the end of trial. Results: Eighty patients completed the trial. After 12-weeks of intervention, subjects in the sumac group showed a greater decrease in hepatic fibrosis and liver enzymes as well as FBS, serum insulin, HbA1c, HOMA-IR, MDA, and hs-CRP, compared to the placebo ( P -value < 0.05); while the QUICKI was significantly higher in the sumac group at the end of intervention. Conclusion: Daily intake of 2000 mg sumac powder along with a low-calorie diet for 12 weeks was beneficial for the management of NAFLD. Highlights: The effect of sumac powder was assessed in patients with non-alcoholic fatty liver disease. Sumac powder improved significantly hepatic fibrosis and glycemic status. Supplementation with sumac was accompanied by a decrease in inflammation and oxidative stress.